As políticas de bonificação em Minas Gerais, Pernambuco e São Paulo: a carreira docente e a contradição com as recomendações do Banco Mundial - Pereira, Mariane Gomes (2022)
The aim of this investigation was to identify and understand the assimilation of World Bank recommendations for teaching work by means of bonus policies in the states of Minas Gerais, Pernambuco and São Paulo, and their repercussions. The interest concerning the World Bank in this study took place since it first appeared with a purpose, but from a specific moment on it became interested in education and started to make recommendations, including for teaching work. Furthermore, the implementation of bonus policies in MG, PE and SP were praised in the document produced and named “Achieving world-class education in Brazil: next steps”. Therefore, the research problem was: what developments in teaching work were brought to this field by bonus policies adopted by MG, PE and SP as a recommendation from the World Bank? Thus, a bibliographic survey of theses, dissertations and scientific articles, found in the Digital Library of Theses and Dissertations (BDTD) at the Brazilian Institute of Information in Science and Technology (Ibict), and in the Scientific Electronic Library Online (Scielo), was carried out. The search made it possible to understand that teacher training has been impacted by neoliberalism as those financed by the World Bank were very short, without reflection, with a utilitarian focus and only aimed at certification. As for teacher training, both initial and continuing, they take place more often in private institutions, being a preference of the World Bank as it considers teachers are better prepared for the demands of the market in these private institutions. Regarding teaching work, there are recommendations to attract better students to teacher training courses with the justification of increasing the quality of teaching. As for remuneration, economists argue that it is not low, as it is compatible with the workload, the hours of work in class. It was possible to identify that there is application of performance evaluation and bonus in Latin America. The documental analysis of three documents from the World Bank enabled this researcher to identify the conception and proposals for teaching work and it could be observed that in the view of this international organization, teaching work must meet the demands imposed by capitalism. In addition to this, the discourse defended by the World Bank is in favor of the adoption of performance evaluation and, consequently, bonuses, as they allow the distinction between “good” and “bad” teachers. This logic leads to individual accountability and regulation of the job. As part of a comparative study, the National Education Plan (PNE) 2014-2024, the state education plans and the Position and Career Plans (PCCs) of MG, PE and SP were analyzed and compared the information found with the information obtained in the analysis of the World Bank documents for teaching. With the results, it was realized that the proposals are divergent, because while one is directed to discussions that value the teaching work, the other one is against this proposal. A last step consisted of a documentary study of the reform proposals in MG, PE and SP, as well as in the respective bonus programs. At the same time, a new bibliographic survey of theses and dissertations to understand the unfolding of the applicability of bonus policies was also carried out. We understand that these programs generated teacher accountability and a teacher reconfiguration because of meritocracy. Therefore, the thesis defended is that the World Bank recommendations, structured by the neoliberal bias, were adopted by the states of MG, PE and SP by means of bonus programs that focused on merit and the effects were individualism and control.